Pelatihan Guru Mengembangkan Pembelajaran yang Menyenangkan, Ilmiah, Kreatif dan Inovatif: Studi Kasus SMA Negeri 1 Tanjung Raja - Lubis, Patricia H.M; Hakim, Lukman; Lefudin, Lefudin; Sugiarti, Sugiarti; Sulistiawati, Sulistiawati; Adelia Fitri, Elsi; Roma Wina, Demi (Universitas PGRI Palembang, 2025)
Teachers as educators in classroom learning have an important role in improving the competence of educators in creating a fun, creative and innovative learning environment. The purpose of this training is to increase understanding and practice ASIK (Active, Scientific, Innovative, and Creative) learning at SMA Negeri 1 Tanjung Raja. The training method includes theory sessions, hands-on practice, and interactive discussions involving teachers at SMAN 1 Tanjung Raja. This activity involved 31 teachers of SMAN 1 Tanjung Raja. The material presented included an introduction to the concept of ASIK, optimization of technology-based learning, and the application of interactive learning media according to the independent curriculum. The results of this training were evaluated and showed that this training succeeded in increasing teachers' understanding of the concept of creative learning and motivation to apply it in teaching and learning activities. This training is expected to be a model in supporting the improvement of the quality of education at the secondary school level and become an additional material for teachers in improving learning in the classroom.